"The great source" microplastic abundance and characteristics along the river Thames. (June 2023) - Devereux, Ria; Ayati, Bamdad; Westhead, Elizabeth Kebede; Jayaratne, Ravindra; Newport, Darryl
Abstract: This study focused on quantifying the abundance of microplastics within the surface water of the River Thames, UK. Ten sites in eight areas were sampled within the tidal Thames, starting from Teddington and ending at Southend-on-Sea. Three litres of water was collected monthly at high tide from land-based structures from each site from May 2019 to May 2021. Samples underwent visual analysis for microplastics categorised based on type, colour and size. 1041 pieces were tested using Fourier transform spectroscopy to identify chemical composition and polymer type. 6401 pieces of MP were found during sampling with an average MP of 12.27 pieces L −1 along the river Thames. Results from this study show that microplastic abundance does not increase along the river. Highlights: Average MP along the River Thames decreased from 2019 (12.27 L −1 ) to 2021 (5.92 L −1 ). Fibres made up 93.27 % of all MPs found within the river The most commonly found polymers were polyvinyl chloride, polystyrene and polychloroprene.